Evaluating the link between attendance and performance in higher education - the role of classroom engagement dimensions - Stefan Buechele (Philipps-University Marburg, School of Business and Economics, 2020)
Does attendance matter? This question is not only the title of several research papers on this topic but has still not been answered conclusively yet. In general, studies find positive but mostly weak correlations between attendance and performance. However, due to technological changes in learning, attendance in higher education seems to lose its importance since students do not have to attend class to get access to course material. The question that arises is whether information on purely descriptive attendance is sufficient to prove positive effects of attendance on performance. This study takes a closer look at the link between attendance and performance, examining classroom engagement dimensions as mediating factors. The results suggest that it does not matter if but rather how students attend class.
Keywords: 330; Studium; Schulbesuch; Bildungsniveau; Schätzung; Deutschland